The increase in varus tilt of the joint line convergence angle under weight-bearing is correlated with medial meniscus extrusion in patients with knee osteoarthrosis - Yosuke Ishii; Akinori Nekomoto; Goki Kamei; Atsuo Nakamae; Takato Hashizume; Kexin Zhu; Miharu Sugimoto; Kohei Matsumura; Makoto Takahashi; Nobuo Adachi (PLoS ONE, 2025)
Background Increased medial meniscus extrusion (MME) in weight-bearing conditions is a critical factor associated with knee osteoarthritis (OA) progression and is not an alternative indicator in nonweight-bearing. This feature is related to mechanical stress. However, its correlation with varus knee alignment, reflecting the loading stress on the medial compartment, is still unknown. This study aimed to determine whether increased MME is associated with varus limb alignment. Method Seventy patients with knee OA were recruited for this cross-sectional study. The MME was assessed using ultrasonography. Knee alignments were determined by whole-leg radiography in the standing position, and factors related to the loading stress on the medial compartment of the knee joint were detected, such as the hip-knee-ankle angle, percentage of the mechanical axis, medial proximal tibial angle, and joint line convergence angle (JLCA). MME and JLCA were evaluated under two conditions: nonweight-bearing and weight-bearing, and the increased values were determined as the difference between the conditions (Δ values). Results MME and JLCA were significantly higher in the weight-bearing condition than in the nonweight-bearing. The described alignment for MME under nonweight-bearing in the liner model was HKAA, where the ΔMME was ΔJLCA. Conclusion The factors of increased MME in weight-bearing conditions differed from those of MME in nonweight-bearing conditions, as shown by the amount of change in JLCA under loading stress.